Behavioral literacy of housewive’s financial management during the covid-19 pandemic - Indar Khaerunnisa (The Accounting Journal of Binaniaga, 2021)
Abstract. The purpose of this research was conducted to analyze the literacy behavior of housewives' financial management by analyzing the difference between the financial management behavior of housewives who have income and housewives who have no income in the city of Bogor, during the Covid-19 pandemic, where it proxied by the knowledge of these housewives about banking, insurance and pawnshops. In addition, this research also uses a quantitative approach, using a questionnaire as a tool to find data. Respondents used as many as 170 people. Consists of housewives who have income and housewives who have no income. Data analysis using Multiple Linear Regression. The results showed that there was a significant influence between the Covid-19 pandemic condition and the behavior of housewives' financial management, either jointly or partially. Meanwhile, the financial management behavior of housewives who have income and housewives who do not have income is different in principle.